2012
DOI: 10.1002/elps.201100462
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic investigation of anti‐tumor activities exerted by sinularin against A2058 melanoma cells

Abstract: The extracts from soft corals have been increasingly investigated for biomedical and therapeutic purposes. The aim of this study is to examine and analyze the anti-tumor effects of the genus Sinularia extract sinularin on A2058 melanoma cells using MTT assay, cell migration assay, wound healing assay, flow cytometric analysis, and proteomic analysis. Sinularin dose-dependently (1-5 μg/mL) inhibited melanoma cell proliferation while the treatment at identical concentrations suppressed cell migration. Sinularin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
58
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 83 publications
1
58
0
Order By: Relevance
“…2,9,24 The concentrations of protein were determined by bicinchoninic acid assay according to the manufacturer's instructions. In all, 10% sodium dodecyl sulfate-polyacrylamide gel electrophoresis was used to run and separate the protein samples.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…2,9,24 The concentrations of protein were determined by bicinchoninic acid assay according to the manufacturer's instructions. In all, 10% sodium dodecyl sulfate-polyacrylamide gel electrophoresis was used to run and separate the protein samples.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…It has been found that several natural compounds from soft corals have cytotoxic and apoptosis-inducing effects against melanoma cells, hepatocellular carcinoma cells, and bladder cancer cells in our previous studies. 2,9,10 Heteronemin (HET) is a known sesterterpenoid extracted from the sponge Hippospongia sp. This natural marine compound was found to inhibit the enzyme protein farnesyltransferase and reduce the viability of leukemia cells, colon cancer cells, and breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations